Coverage Differentiation Based Adaptive Tx-Power for Congestion and Awareness Control in VANETs - Ali Shah, Syed Adeel; Ahmed, Ejaz; Xia, Feng; Karim, Ahmad; Qureshi, Muhammad Ahsan; Ali, Ihsan; Noor, Rafidah Md (Springer Verlag, 2018)
The use of Information and Communication Technology (ICT) as a copilot for the drivers has a potential to improve traffic safety and efficiency. A key challenge in integrating ICT in vehicular networks is to provide the mechanisms for the delivery of safety messages called beacons. In particular, finding the trade-off between providing sufficient coverage and controlling channel congestion remains the focus in the stipulated amendments for safety message transmissions. In this paper, we handle this trade-off by proposing a Multi-metric Power Control (MPC) approach, which uses application requirements and channel states to determine a transmit power for safety messages. The MPC gives a best-effort approach to satisfy the coverage range requirement of a message as specified by the application. Moreover, the concept distinguishes among message types to provide coverage differentiation. We show that the best-effort approach of providing coverage for different messages can control congestion and as a result improve awareness by minimizing beacon collisions. The performance analysis of MPC using discrete event simulation confirms its practicality.